When the Artificial Is Natural: Reconsidering What Bionics and Sensoria Do. (27th January 2021) - Lloyd, Stephanie; Bonventre, Chani
Abstract: When the artificial is natural: reconsidering what bionics and sensoria do. Videos of cochlear implant (CI) activation are common on online platforms such as YouTube, presenting activation as a "magical" moment when people receive "the gift of hearing." We argue that these videos present a distorted understanding of what bionic devices, specifically CIs, do. Our research focuses on the scientific understandings of what the implants do within a user's sensorium and, consequently, what people do with CIs. The case of CIs calls us to analyze and subvert notions of sensory deficits and the bionic devices that are thought to repair them. In doing so, we delve into the forms of embodiment and processes associated with "hearing, " in its multiple forms. We examine the categories of artificial and natural, and how they relate to researchers' and clinicians' conceptualizations of the sensoria of people with CIs. This approach turns attention back to the people living with CIs themselves and is positioned antithetically to the "inspiration porn" of viral CI activation videos, compelling us to consider how people who use CIs create and inhabit new 'natures' with the devices. Quand l'artificiel est naturel: repenser la relation entre appareils "bioniques" et sensorium. Les vidéos d'activation d'implants cochléaires (ICs) sont devenus du contenu courant, voire viral, sur des plateformes en ligne comme YouTube. L'activation y est très souvent présentée comme un moment « magique », qui permet à la personne de recevoir l'audition comme un « don ». Mais dans quelle mesure cette représentation correspond‐elle vraiment aux expériences présentées dans, et au‐delà de ces vidéos ? Cet article explore ce que font les ICs, en tant qu'appareils « bioniques » une fois intégrés dans le sensorium d'une personne et, conséquemment, quelle part prennent les personnes utilisant des ICs à ce processus. À travers ces questionnements, nous proposons d'analyser et subvertir les notions de déficit sensoriel et l'idée selon laquelle des appareils bioniques seraient capables de les réparer. En se tournant vers les formes d'incorporation ( embodiment ) et les processus associés à l' « audition » dans ses formes multiples, nous examinons comment les notions d'artificiel et de naturel induisent une conceptualisation spécifique et réductrice du sensorium. Cette approche vise à valoriser l'expérience des personnes vivant avec des ICs et se positionne ainsi en opposition à l' « inspiration porn » sous‐jacente aux vidéos virales d'activation d'ICs. Notre objectif est de considérer comment la diversité des expériences des personnes vivant avec des ICs renseigne les 'natures' multiples de l'audition, et plus spécifiquement celles produites au sein d'assemblages qui comprennent des appareils technologiques.